Natural Antioxidants in Foods and Medicinal Plants: Extraction, Assessment and Resources - Xu, Dong-Ping; Li, Ya; Meng, Xiao; Zhou, Tong; Zhou, Yue; Zheng, Jie; Zhang, Jiao-Jiao; Li, Hua-Bin (International journal of molecular sciences, 2017)
Natural antioxidants are widely distributed in food and medicinal plants. These natural antioxidants, especially polyphenols and carotenoids, exhibit a wide range of biological effects, including anti-inflammatory, anti-aging, anti-atherosclerosis and anticancer. The effective extraction and proper assessment of antioxidants from food and medicinal plants are crucial to explore the potential antioxidant sources and promote the application in functional foods, pharmaceuticals and food additives. The present paper provides comprehensive information on the green extraction technologies of natural antioxidants, assessment of antioxidant activity at chemical and cellular based levels and their main resources from food and medicinal plants.